What is the Role of Testosterone Therapy in Postmenopausal Women? A SWOT Analysis - Fatih Aktoz; Ali Can Gunes; Cemal Tamer Erel (IMR Press, 2023)
Objective: The objective of this review is to examine the current state of evidence on postmenopausal testosterone use in women and explore its potential benefits and risks using the SWOT analysis method which is an evaluation system that allows reviewing any issue under the headings of strengths, weaknesses, opportunities and threats. Mechanism: Testosterone plays a role in female sexual physiology through its effects on the brain and peripheral tissues. At the central level, it stimulates regions of sexual function and interacts with specific receptors in the brain to regulate sexual desire, arousal, and satisfaction. At the peripheral level, testosterone affects various tissues and organs that are involved in sexual function, including the vagina, clitoris, and labia. Testosterone interacts with the androgen receptor in cells and triggers various physiological responses depending on the tissue. It stimulates sperm production in the testes, promotes bone growth and maintenance, and increases muscle mass and strength through protein synthesis. Testosterone also has a beneficial effect on bone density and the cardiovascular system, reducing the risk of heart disease and stroke. It influences cognitive functions such as memory, processing speed, and executive function through androgen receptor-regulated regions of the brain. Findings in Brief: Postmenopausal testosterone therapy may improve sexual function, muscle mass, and reduce the risk of osteoporosis. However, its long-term safety and effectiveness are still under debate. Testosterone therapy can be effective in treating certain symptoms in postmenopausal women, but it may also increase the risk of cardiovascular events and endometrial cancer, and can lead to adverse symptoms such as acne and hirsutism. Careful monitoring and regular hormone level checks are necessary to ensure safe and effective use. It's important to consider the potential risks and benefits when deciding whether testosterone therapy is appropriate for a postmenopausal woman. Conclusions: Testosterone therapy in postmenopausal women may be a valuable treatment option for selected women. However, more research is needed to better understand the long-term effects of its use. Further research may also help to determine optimal dosing and route of administration, as well as specific testosterone preparations for women.